Queuing Theory And immigration process at Kempe Gowda international airport (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This paper study the immigration process at Kempe Gowda international airport and how we can use queueing model to make immigration process more comfortable in less time consuming.